Islamic revivalism and politics in post Suharto Indonesia : A study of PARTAI KEADILAN SEJAHTERA (PKS, the prosperous justice party) - Wahyudhi , Nostalgiawan (Kulliyyah of Islamic Reveal Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This thesis addresses the issue of contemporary Islamic revivalism and politics in Post-Suharto Indonesia, with special reference to the role of Partai Keadilan Sejahtera (PKS, the Prosperous Justice Party). It studies the origin of the party, its ideology, structure and political platform; and explains why they had changed in post-Suharto Indonesia. Based on Douglas C. North theory of transactional cost world', the study argues that the dynamics of the Indonesian democratic political environment have determined the strategy of PKS. Political constraints create transactional politics that triggered the party to adjust its ideology and structures to the prevailing political needs in order to increase its electability. The discourse maintains that, firstly, the revivalist party has roots in Indonesian politics and takes lessons from the experience of two Indonesian Islamic organizations, namely Sarekat Islam (Muslim Union) and Masyumi (The Shūrā Council of Muslim Indonesians). Secondly, the party has an ideological linkage to the Muslim Brotherhood of Egypt. Finally, in order to maximize its electoral appeal, the PKS adjusted its ideology and structure to the needs and interests of the core electorate. It shifts its ideology to the centre of political spectrum as an inclusive nationalist-religious party, which is close to the character of a catch-all party. On the other hand, it still maintains the character of a mass party by embracing Islam through the Muslim Brotherhood's cadre system.